PERCEPTIONS AND BEHAVIORS OF LP3I JAKARTA POLYTECHNIC STUDENTS AT THE DEPOK CAMPUS IN CHOOSING ONLINE OJEK AS A DAILY TRANSPORTATION MEANS (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
This research was conducted to find out how students of Politeknik LP3I Jakarta Depok Campus perceive and behave in choosing online motorcycle taxis as their daily transportation. The results of this study were obtained through in-depth interviews with several students of Politeknik LP3I Jakarta Depok Campus who frequently use online motorcycle taxis in their daily activities. The results show that students who actively use online ojek applications are more interested in using the Grab app to support their college activities. The choice is influenced by several internal factors such as promotions and ease of access, as well as external factors like excellent driver service. Complaints they experienced include difficulty finding drivers during bad weather, incomplete supporting facilities, drivers’ unfriendly attitudes, not properly ensuring passenger safety, and fairly long order times.